(3GdQjGVs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Efg bO SHb dfG bHd cJGHfG gPG YOI cJH ai gPg GdCUhd LejYgG eHOOI s
(3BNQgG (B:s
(3hbO GTJedJ Ydi LejY bhGYO GdUfYI YdeG hYedG Je GdLRA GdYTQhf HJeGeg Je cJGH GdQjGV s
(3Vef eLehY , JQJjHgG (B: (3ef U (B158 - (3U(B196s
(3hgj YHGQI Yf YTQhf LRAkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B126 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdcjejGA h GdWHjYjGJs